Approaching the Forming Environment of Shelly Chenier in the West Coast of Bohai Bay: exemplified by Chenier III in Yucenzi site. Issue 4 (April 2020) - Jing, Fang; Zhiwen, Shang; Wang, Fu; Yang, Li; Zhang, Liping; Yang, Shuo; Wang, Tianjiao; Liu, Yufei; Yang, Yongqiang
Abstract: In order to explore the causes of formation of the cheniers on the west coast of Bohai Bay, the Yucenzi chenier near the third chenier on the West Coast Plain of Bohai Bay is taken as the research object, and drilling investigations of the sediment under the Yucenzi chenier was conducted to measure the conductivity of the slime turbid water and identify the foraminifera of the drilling samples. The results showed that the underlying sediments of Yucenzi chenier are formed by a 534m thick continental sedimentary layer, and the chenier does not contact with the marine or transitional sedimentary layer directly. It can be inferred that the Yucenzi chenier belonging to the third chenier is formed through shells accumulated on the supratidal zone during storm tide or spring tide.